ABSENNYA NEGARA DALAM PERSPEKTIF MARXISME DI PENAMPUNGAN DVD GLODOK - Rido Budiman (Fakultas Komunikasi, Sastra, dan Bahasa, 2012)
This article discuss about the absencence of state as law enforcer in public order in context of Indonesia especially in Glodok area, Jakarta. The State through the institution such as police, judge, and attorney function as law enforcer of rules and bills produced by legislative institution such as parliament, nevertheless in some cases like Glodok there are some dysfunction of state institution. In discussing this problem I intend to use Marxism perspective in viewing state function as it should be. I use qualitative methods in researching the facts in field by observation and interviews related sources and I am going to analyze the results by using Karl Marx theory in viewing the state.